Parental knowledge and attitude of postoperative paediatric pain: stepwise linear regression analysis - Desalegn, Mitiku; Shitemaw, Tewoderos; Getahun, Genanew Kassie; Lemma, Lire (Frontiers in Pain Research, 2024)
Background Despite the fact that mothers care for their children's pain in most cases, it has been noted that mothers have limited knowledge and attitude about paediatric pain. This study aims to assess parental knowledge and attitude of postoperative paediatric pain (POPP). Method This is institutional based cross sectional study conducted with 102 parents at Nigist Eleni Mohamed Memorial Comprehensive Specialized Hospital (NEMMCSH). A convenience sampling technique was used to select parents. This study has used a questionnaire (Parental Pain Expression Perception (PPEM), examine parents' attitudes and knowledge about how their children exhibit their pain and Medication Attitude Questioner (MAQs), focuses on how parents feel about giving their child analgesic medication to alleviate post-operative pain). Descriptive statistics were utilized to analyse the parent's response and presented with frequency and percentage. Factor analysis to analyze factor structure and stepwise linear regression analysis to examine the impact of socio-demographic factors in predicting parental knowledge and attitude about POPP were done. The statistical tests were performed at 95% confidence interval and 5% significance level. Result A total of 102 parents fulfilling the inclusion criteria were included. About 78% of parents agreed that children always express pain by crying or whining. The majority of parents (75.6%) believe children who are playing are not in pain. Regarding parental attitudes about pain medications, majority of parents (61%) believe that children should be given pain medication as little as possible because of its side effects. According to about 26.8% of parents, giving children pain medication for pain might teach them to use drugs for other issues. On the other hand, 63.4% of parents say that giving children pain medication as little as possible is the most effective way to manage their pain. Parents of younger children and parents from rural area are more likely to score higher in attention seeking sub-score of PPEP while parents from urban residence and those parents who are employed are more likely to perceive about the side effects of pain medications (Side effects factors). Conclusion The overall knowledge and attitude of parents about postoperative pain and pain medications were poor.